Acid-sensing ion channels detect moderate acidifications to induce ocular pain. Issue 3 (March 2015) - Callejo, Gerard; Castellanos, Aida; Castany, Marta; Gual, Arcadi; Luna, Carolina; Acosta, M. Carmen; Gallar, Juana; Giblin, Jonathan P.; Gasull, Xavier
Abstract : Abstract: Sensory nerve fibers innervating the ocular anterior surface detect external stimuli producing innocuous and painful sensations. Protons are among the first mediators released by damaged cells during inflammation, tissue injury, or other chronic ophthalmic conditions. We studied whether acid-sensing ion channels (ASICs) are expressed in corneal sensory neurons and their roles in the response to moderate acidifications of the ocular surface and in pathologies producing ocular surface inflammation. Moderate acidic pH (6.6) activated ASIC-like currents in corneal sensory neurons, which were blocked by ASIC1- or ASIC3-specific toxins. Acidic pH depolarizes corneal sensory neurons to fire action potentials, an effect blocked by the ASIC3 inhibitor APETx2. 2-Guanidino-4-methylquinazoline, an ASIC3 agonist, activated a population of corneal polymodal sensory nerve fibers and significantly increased the blinking and tearing rate. The nocifensive behaviors produced by application of either a moderate acidic stimulus or ophthalmic drugs formulated in acidic solution were abolished by ASIC blockers. In a model of allergic keratoconjunctivitis, nocifensive behavior was greatly reduced by ASIC3 blockade, presumably by reducing nociceptor sensitization during the inflammatory process. Our results show that, in addition to the established role of TRPV1, ASICs play a significant role in the detection of acidic insults at the ocular surface. The identification of ASICs in corneal neurons and their alterations during different diseases is critical for the understanding of sensory ocular pathophysiology. They are likely to mediate some of the discomfort sensations accompanying several ophthalmic formulations and may represent novel targets for the development of new therapeutics for ocular pathologies. Abstract : Corneal sensory nerves express different types of acid-sensing ion channels that detect moderate acidifications of the ocular surface and mediate ocular painful responses.